2020
DOI: 10.32552/0.actamedica.490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Compliance of Different Iron Chelators Including Original and Bioequivalents of Deferasirox

Abstract: Objective: The current iron chelation therapy regimens include deferoxamine (DFO), deferiprone (DFP), and deferasirox (DFX) in transfusion-dependent patients. Compliance with iron-chelating therapy is one of the significant determinants of mortality and morbidities related to iron loading in chronically transfused patients. This survey aims to compare the compliance and the satisfaction of DFO, DFP, and DFX formulations in patients who have iron-overloading in three hematology centers from Turkey. Moreover, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…21 Given its recent introduction, there is little published evidence on generic deferasirox. 22 One prospective study in Indonesia found locally produced generic deferasirox noninferior to the brand name for reducing iron levels and serum ferritin over 1 year. Affordability was improved.…”
Section: Deferasiroxmentioning
confidence: 99%
“…21 Given its recent introduction, there is little published evidence on generic deferasirox. 22 One prospective study in Indonesia found locally produced generic deferasirox noninferior to the brand name for reducing iron levels and serum ferritin over 1 year. Affordability was improved.…”
Section: Deferasiroxmentioning
confidence: 99%